2010
DOI: 10.1093/brain/awq190
|View full text |Cite
|
Sign up to set email alerts
|

Microseizures and the spatiotemporal scales of human partial epilepsy

Abstract: Focal seizures appear to start abruptly and unpredictably when recorded from volumes of brain probed by clinical intracranial electroencephalograms. To investigate the spatiotemporal scale of focal epilepsy, wide-bandwidth electrophysiological recordings were obtained using clinical macro- and research microelectrodes in patients with epilepsy and control subjects with intractable facial pain. Seizure-like events not detectable on clinical macroelectrodes were observed on isolated microelectrodes. These 'micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
256
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(272 citation statements)
references
References 28 publications
14
256
2
Order By: Relevance
“…These observations suggest the local generation of gamma-IEDs, reminiscent of "microdischarges" that can propagate into widespread epileptiform discharges visible on clinical macroelectrodes. 8 The gamma-IEDs could thus mark the IED source, and illuminate the mechanisms underlying IED generation-a hypothesis that will need to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest the local generation of gamma-IEDs, reminiscent of "microdischarges" that can propagate into widespread epileptiform discharges visible on clinical macroelectrodes. 8 The gamma-IEDs could thus mark the IED source, and illuminate the mechanisms underlying IED generation-a hypothesis that will need to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, if ictogenesis is a rather spatially local mechanism in the seizure onset zone, electrode contacts need to be abundant enough to cover a large volume (covering the seizure onset zone) and able to record from small enough volume in order to pick up any preictal change. Such electrode contacts do exist in the form of micro-contacts (Kelly et al, 2007;Stead et al, 2010) and studies on seizure prediction analysing data recorded with these electrodes are expected to provide answers to important questions on seizure predictability.…”
Section: Discussionmentioning
confidence: 99%
“…These functional data are supported by the demonstration that the histopathological damage in mesial TLE cannot be considered "focal," because it includes different hippocampal and parahippocampal structures with variable rostrocaudal extension (Moran et al 2001;Ogren et al 2009;Tassi et al 2010). Finally, intracranial microelectrode recordings in humans have shown that partial seizure may initiate in different areas or microregions within the epileptogenic zone (Stead et al 2010), suggesting that the paroxysmal activity generated at distant sites within an epileptogenic network contributes to ictal onset patterns observed with the diagnostic macroelectrodes (Bartolomei et al 2001;Wendling et al 2003).…”
mentioning
confidence: 99%